An update on complementary feeding - Warren, Janet (Nursing children and young people, 2018)
Complementary feeding is an important developmental milestone in children and occurs at a formative time for the development of healthy eating habits that can continue into later childhood and beyond. The timing of weaning has been a controversial subject and recommendations in the UK differ from those in Europe. In the UK and New Zealand, baby-led weaning is becoming increasingly popular. The importance of responsive feeding is highlighted to make parents aware of a baby's cues indicating hunger or fullness. There have also been advances in the science of immunology that deem the early introduction of allergens to be a preventive strategy for food allergies. This article discusses the nutritional requirements for infants and reviews the foods that should be introduced and avoided. Guidelines are changing all the time, so nurses must keep up to date with current research to be able to offer advice to parents of infants.